Reception of academics toward the film Dirty Vote in the context of the 2024 general election - Muhamad Rosit; Gede Munanto; Maryan Engeline (Privietlab, 2025)
This study examines the academic reception of the documentary film Dirty Vote. The film exposes the misuse and partiality of political power during the 2024 general election contestation. Using a qualitative research approach, this study uses Stuart Hall’s theory of audience reception, especially the ideas of encoding and decoding. Seven academics from various universities, each with expertise in political communication and media studies, were interviewed for data collection. The results show various interpretations by the informants. Four informants chose a dominant-hegemonic position, interpreting Dirty Vote as a form of political literacy and a critique of government abuse. Two informants took a negotiated position, viewing the movie as both a medium for political literacy and a potential for political propaganda in the lead-up to the 2024 presidential general election. Meanwhile, one informant represented an oppositional position, perceiving the movie as biased and politically motivated. In conclusion, Dirty Vote Movie functions as a space for interactive discussion between the media, government, and academic universities, affirming that media products can simultaneously foster awareness and provoke ideological debate within a democratic society.